Rare occurrence of palatal perforation in a case of leprosy: a case report and literature review - Gonnuru, Vinod Kumar; Dandala, Sridhar Reddy; Albi, Irene; Abbugari, Rudrakshini; Bhaskar, Jaya; Varma, Varaprasada (International Journal of Research in Medical Sciences, 2023)
The aim of the study was to demonstrate the rare occurrence of coexistent nasal septal and palatal perforations in a case of lepromatous leprosy. Nasal septal perforation is a full-thickness defect of the nasal septum which includes the bilateral mucoperichondrial flaps and structural middle layer. It occurs mostly on the anterior cartilaginous septum. Most of the patients are asymptomatic and the two-third of the people affected show no nasal complaints. Palatal perforation is said to have occurred when there is a development of communication between bilateral nasal cavities and the oral cavity. Whereas in our case, septal perforation was found to be co-existent with palatal perforation which is a rare condition. A 32-year-old, otherwise healthy patient presented with complaints of nasal regurgitation of food contents and shortness of breath while eating for 3 months. Septal mucosal biopsy, biopsy from the palatal perforation and the left ear nodule was taken without any complications, and tissue was sent for histopathological examination which showed features suggestive of lepromatous leprosy. The occurrence of coexistent septal and palatal perforation is rare and it is even rarer to be found in a case of lepromatous leprosy. Hence proper history should be elicited and adequate investigations such as histopathological examination should be performed in cases of coexistent nasal septal and palatal perforation.